Strategic Management of Cocoa Marketing in The Plea Puli Multipurpose Cooperative in East Nusa Tenggara - Matheus Frynardo Keukama; I Gusti Agung Ayu Ambarawati; I Nyoman Gede Ustriyana (JURNAL MANAJEMEN AGRIBISNIS, 2020)
Cacao plays an important role in the Indonesian economy. One of the business entities engaged in cocoa commodity business activities is the Plea Puli Multipurpose Cooperative (KSU). The low number of cocoa purchases at the KSU Plea Puli is caused by various factors. One of them is competition with other cocoa buyers. Related to efforts to increase cocoa marketing, it is necessary to first know about the cocoa supply chain to the KSU Plea Puli. The purpose of this study is to analyze the cocoa supply chain to the KSU Plea Puli and strategies that can be implemented in increasing cocoa marketing. The study was conducted at KSU Plea Puli in East Nusa Tenggara. The main research instrument is a questionnaire. The determination of respondents to determine the cocoa supply chain to the KSU Plea Puli was conducted on member farmers using the Slovin formula and non-member farmers using quota sampling techniques. The number of respondents in this study were 60 people. The determination of informants to find out the cocoa supply chain to the KSU Plea Puli and the informants determining internal and external strategic factors was done purposively. The results showed that in the cocoa supply chain to the KSU Plea Puli, there were three types of flows managed, namely material, financial and information flows. The parties involved consisted of member farmers and not members and the KSU Plea Puli themselves. In addition, there are various activities carried out such as cocoa production and marketing by farmers and cocoa marketing operations by KSU Plea Puli. The results also show that 12 alternative strategies are possible to support efforts to increase cocoa marketing by increasing the number of purchases. Strategy priority based on the highest-ranking with a score of 5.75 that is giving special authority to managers to carry out cocoa marketing operations. The management is expected to be able to implement the results of the strategic management of cocoa marketing in the KSU Plea Puli with the priority of the strategy being to give special authority to the manager to carry out cocoa marketing operations. The existence of the Commodity Product Processing and Marketing Unit (UPPH) at the KSU Plea Puli needs to be maintained and developed. Farmers are expected to adopt good agricultural practices by implementing PsPSP which consists of frequent harvesting, pruning, sanitation, fertilization and soil, and plant health and pest and disease control. In addition, farmers are also encouraged to always maintain the quality of cocoa beans. Keywords: strategic management, supply chain, cocoa